Transport demand as a function of the state of a transport network - T. Sakulyeva (Управление)
For thousands of years in major cities one of the main problems was the possibility of movement. The need for movement is based on the opportunities provided by transport, and encourages society to further develop. The article considers the historical aspects of the study of the mobility of the population and the study of its mobility in terms of digital technology.The application of various methods of mobility research is a common practice in many countries, cities, regions, which provides the collection of important information for the development of transport systems. Financial and organizational constraints affect the quantity and quality of the data collected. Existing techniques need to be constantly adapted to rapidly developing technologies and the rapidly changing nature of population mobility, which is becoming more intermodal. A qualitative model based on an appropriate data set creates a qualitative set of input data for the concept, design, and evaluation results. This in turn will allow for a more reasonable design and evaluation of transport projects.Transport modeling varies from developing relatively simple models in the form of tables to models of transport networks, which consider transport demand as a function of the state of the transport network. For each stage of modeling, there is a need to include feedback in the modeling process. They reveal the interrelation of the various steps of the modeling process and the need to use iterative methods of calculation. The functionality of the model is determined by the presence of feedbacks, which increase the ability of the model to predict actual results. Before carrying out any actions on transport modeling, it is necessary fully understand the requirements for the function of this model. This will ensure, that the model is a result, which is important for the project and provides it with a qualitative assessment.